Impact of lay health worker programmes on the health outcomes of mother-child pairs of HIV exposed children in Africa: A scoping review. - Kathrin Schmitz; Tariro Jayson Basera; Bonaventure Egbujie; Preethi Mistri; Nireshni Naidoo; Witness Mapanga; Jane Goudge; Majorie Mbule; Fiona Burtt; Esca Scheepers; Jude Igumbor (PLoS ONE)
Background Increased demand for healthcare services in countries experiencing high HIV disease burden and often coupled with a shortage of health workers, has necessitated task shifting from professional health workers to Lay Health Workers (LHWs) in order to improve healthcare delivery. Maternal and Child Health (MCH) services particularly benefit from task-shifting to LHWs or similar cadres. However, evidence on the roles and usefulness of LHWs in MCH service delivery in Sub-Saharan Africa (SSA) is not fully known. Objectives To examine evidence of the roles and impact of lay health worker programmes focusing on Women Living with HIV (WLH) and their HIV-exposed infants (HEIs). Methods A scoping review approach based on Arksey and O'Malley's guiding principles was used to retrieve, review and analyse existing literature. We searched for articles published between January 2008 and July 2018 in seven (7) databases, including: MEDLINE, Embase, PsycINFO, Joanna Briggs, The Cochrane Library, EBM reviews and Web of Science. The critical constructs used for the literature search were "lay health worker", "community health worker", "peer mentor", "mentor mother," "Maternal and Child health worker", "HIV positive mothers", "HIV exposed infants" and PMTCT. Results Thirty-three (33) full-text articles meeting the eligibility criteria were identified and included in the final analysis. Most (n = 13, 39.4%) of the included studies were conducted in South Africa and used a cluster RCT design (n = 13, 39.4%). The most commonly performed roles of LHWs in HIV specific MCH programmes included: community engagement and sensitisation, psychosocial support, linkage to care, encouraging women to bring their infants back for HIV testing and supporting default tracing. Community awareness on Mother to Child Transmission of HIV (MTCT), proper and consistent use of condoms, clinic attendance and timely HIV testing of HEIs, as well as retention in care for infected persons, have all improved because of LHW programmes. Conclusion LHWs play significant roles in the management of WLH and their HEIs, improving MCH outcomes in the process. LHW interventions are beneficial in increasing access to PMTCT services and reducing MTCT of HIV, though their impact on improving adherence to ART remains scanty. Further research is needed to evaluate ART adherence in LHW interventions targeted at WLH. LHW programmes can be enhanced by increasing supportive supervision and remuneration of LHWs.